Photoelectric properties of n-SiC/n-Si heterojunctions - Semenov, A. V.; Kozlovskii, А. А.; Puzikov, V. M. (Technology and design in electronic equipment, 2012)
Photovoltaic effect in isotype heterotructure formed by nanocrystalline silicon carbide films on single crystal n-Si substrates (n-SiC/n-Si heterojunction) was studied. The films were produced by direct ionic deposition method. The model that takes into account the quantum wells and potential barriers caused by band offsets was proposed to explain the current-voltage characteristics and photovoltaic properties of the heterostructure n-SiC/n-Si.